Pengujian Mikroba pada Belut Kering (Kepanjang) Berdasarkan Pengaruh Lama Penyimpanan dan Suhu Lingkungan terhadap Kontaminasi Mikroba - Okti Sonya Rahmadani; Ardi Mustakim (International Forum of Researchers and Lecturers, 2025)
Dried eel (kepanjang) is a traditional food product made through the drying process to extend shelf life and facilitate distribution. While drying can slow down product deterioration, it still carries the risk of microbial contamination, especially when stored at room temperature without additional preservation. This study aims to provide information regarding the microbiological safety of dried eel products during storage and to determine the effects of storage duration and environmental temperature on microbial growth in dried eel. The method used in this study involved direct observation of microbial colony growth through serial dilution and inoculation on Nutrient Agar (NA) media, which was then incubated at room temperature. The microbial colonies growing on the dried eel samples were observed and counted to assess the impact of storage duration and temperature on microbial contamination. The results showed that the longer the storage time and the higher the environmental temperature, the greater the number of microbial colonies that grew. This indicates that storage conditions, both in terms of duration and temperature, have a significant impact on the level of microbial contamination in dried eel. This research reveals the importance of strict monitoring of temperature and storage duration for dried eel products. The increase in microbial colonies as storage time and temperature rise indicates that the product becomes more susceptible to contamination and spoilage. Therefore, to maintain product quality and safety, proper storage systems need to be implemented, such as using additional preservatives or storing the product at low temperatures. By adopting these measures, the risk of microbial contamination can be minimized, which will extend the shelf life and maintain the quality of the dried eel product. This study provides valuable insights into the microbiological aspects of traditional food products, specifically dried eel, which can be applied to ensure their safety during storage.